Manufacturing companies' risk perception based on the influence of safety leadership, safety knowledge, and safety attitudes. - Putranti, Latifah; Saputri, Arista Yesi; Aryandha, Pradita Nindya; Herdiany, Hapsari Dyah (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
The growth and development of the manufacturing industry certainly has a positive impact because it increases employment, but it is directly proportional to the increase in work accidents. Most of the causes of work accidents are unsafe behavior. Unsafe behavior is caused by several factors and risk perception is an important part of it. Risk perception is relevant to safety because it can influence behavior that can influence the likelihood of accidents. This study aims to determine the effect of safety leadership, safety knowledge, and safety attitudes on perceived risk probability and perceived risk severity. This research was conducted at PT Linggarjati Mahardika Mulia in 2022. The sample used in this study was 315 respondents and used non-probability sampling techniques through a purposive sampling approach. The data analysis technique in this study used structural equation modeling with SEM-PLS and WarpPLS 8.0. The results confirmed that safety leadership has a positive effect on perceived risk probability and perceived risk severity. Safety knowledge has a positive effect on perceived risk probability and perceived risk severity. Safety attitude has a positive effect on perceived risk probability and perceived risk severity.